Crafting social integration?: welfare state and volunteering across social groups and policy areas in 23 European countries - Ackermann, Kathrin; Erhardt, Julian; Freitag, Markus (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
The beneficial role of voluntary work for social integration makes it an important aspect of social cohesion. Thus, there is broad interest in understanding the individual and contextual foundations of volunteering. With regard to the latter, a particular focus is on the role of policies and institutions of the welfare state. They might set incentives for civic engagement and create new scope for voluntary work (crowding-in thesis), but they might also make it redundant (crowding-out thesis). We follow the argument that generous welfare states enable volunteering and assume that two mechanisms are at work. First, they establish a general culture of helping and caring for others in a society (cultural mechanism). Second, they provide those who benefit or potentially benefit from welfare state policies with resources and the abilities to engage in volunteering (resource mechanism). Thus, welfare benefits in specific areas of the welfare state are expected to increase volunteering among members of targeted groups (e.g., the elderly if pensions are high). To test these arguments, our empirical analysis combines country-level data of area-specific welfare benefits with survey data of around 29,000 respondents from 23 countries included in the most recent European Value Survey 2017/2018. We estimate hierarchical regression models with cross-level interactions to test whether particular groups of society are activated by general and area-specific welfare programs to become volunteers. Our findings show that volunteering is generally higher in more generous welfare states, lending support to the crowding-in thesis. Area- and group-specific analyses indicate that the resource mechanism works for some groups but not for all. Pension welfare strengthens volunteering among the retired and the elderly. Unemployment welfare reinforces volunteering among the less educated, but these results are slightly less robust, and we do not find support for higher levels of volunteering among the actually targeted group of unemployed persons.
Gesehen am 24.01.2024